2017
DOI: 10.1111/jhn.12506
|View full text |Cite
|
Sign up to set email alerts
|

Food and functional dyspepsia: a systematic review

Abstract: Wheat and dietary fats may play key roles in the generation of FD symptoms and reduction or withdrawal eased symptoms. Randomised trials investigating the roles of gluten, FODMAPs (fermentable oligosaccharide, disaccharide, monosaccharide and polyols) and high fat ingestion and naturally occurring food chemicals in the generation of functional dyspepsia symptoms are warranted and further investigation of the mechanisms is now required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 50 publications
3
66
0
18
Order By: Relevance
“…The relationship between functional dyspepsia and SR‐NCWS is less clear. Both gluten and fructans have been associated with functional dyspepsia in observational studies, and some patients with functional dyspepsia were found to have formal non‐coeliac gluten or wheat sensitivity in dietary crossover trials . Duodenal eosinophilia occurs in people with functional dyspepsia or non‐coeliac gluten or wheat sensitivity, suggesting a pathophysiological link …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between functional dyspepsia and SR‐NCWS is less clear. Both gluten and fructans have been associated with functional dyspepsia in observational studies, and some patients with functional dyspepsia were found to have formal non‐coeliac gluten or wheat sensitivity in dietary crossover trials . Duodenal eosinophilia occurs in people with functional dyspepsia or non‐coeliac gluten or wheat sensitivity, suggesting a pathophysiological link …”
Section: Discussionmentioning
confidence: 99%
“…Often, these are sought out by readers who want to capture the overview of a topic and so, by stating that it is a review in your title, you draw your work to their attention. Food and functional dyspepsia: a systematic review , for example, leaves no doubt about the content of the paper.…”
Section: Think About What Will Sell Your Papermentioning
confidence: 99%
“…При высокой резистентности к фторхинолонам в данном регионе рассматриваются комбинация «ИПП + рифабу-тин + препарат висмута» или другие схемы [23].…”
Section: антихеликобактерная терапияunclassified
“…Развитие микроскопиче-ского воспаления может быть связано с перенесенной пищевой токсикоинфекцией [21], повторными воздействи-ями раздражителей, а также хеликобактерной инфекцией (в последнем случае более корректно, как уже говорилось выше, применять термин «диспепсия, ассоциированная с инфекцией H. pylori») [22]. Среди пищевых факторов, кото-рые могут способствовать развитию микроскопического воспаления при ФД, основная роль принадлежит повы-шенному потребления жиров, ферментируемых углеводов, пшеницы и, возможно, других компонентов, выступающих в роли аллергенов, а также действию соляной кислоты [19,23,24]. Клинические симптомы становятся более выражен-ными в условиях тревоги, депрессии, на фоне повышения метаболизма в таламусе, островке, поясной извилине [25].…”
unclassified
See 1 more Smart Citation